Conjuring up the correspondence of high-school students’ self-determination and classroom climate with reading achievement - Joulide, Shahrbanoo; Faravani, Akram; Boori, Ali Akbar (English Language Teaching Educational Journal, 2020)
A prevalent goal of education in schools is reading comprehension enhancement. Therefore, a critical issue in   educational psychology is investigating the factors contributing to increase the reading achievement including both classroom climate and self-determination. This study explored the relationships of Iranian High School students’ self-determination and classroom climate with their reading achievement.  150 Iranian (male and female) students from Sama and Fazele high schools in Mashhad were selected through convenience sampling. The instruments were IOWA self-determination, Classroom Climate Questionnaires, and a validated researcher-made test. It was a type of quantitative and correlational research. Results revealed a significant and positive relationship between self-determination and reading ability. They also showed that among the six subscales of the self-determination, financial management had a significant relationship with the reading achievement scores of students. However, the emotional independence of peers had a negative correlation with the reading achievement scores of students. The results showed that teachers’ skill in orienting tasks can enhance reading achievement score and make the classroom climate more motivating. This study has potentially helpful implications for English language teachers, English institutes, and students. Teachers can enhance student’s self-determination by providing a friendly classroom environment and indirectly boost the students’ reading score.